CD44 In Sarcomas: A Comprehensive Review and Future Perspectives - Fernández-Tabanera, Enrique; Melero-Fernández de Mera, Raquel M.; Alonso, Javier (Frontiers in Oncology, 2022)
It is widely accepted that the tumor microenvironment, particularly the extracellular matrix, plays an essential role in the development of tumors through the interaction with specific protein-membrane receptors. One of the most relevant proteins in this context is the transmembrane protein CD44. The role of CD44 in tumor progression, invasion, and metastasis has been well established in many cancers, although a comprehensive review concerning its role in sarcomas has not been published. CD44 is overexpressed in most sarcomas and several in vitro and in vivo experiments have shown a direct effect on tumor progression, dissemination, and drug resistance. Moreover, CD44 has been revealed as a useful marker for prognostic and diagnostic (CD44v6 isoform) in osteosarcoma. Besides, some innovative treatments such as HA-functionalized liposomes therapy have become an excellent CD44-mediated intracellular delivery system for osteosarcoma. Unfortunately, the reduced number of studies deciphering the prognostic/diagnostic value of CD44 in other sarcoma subgroups, neither than osteosarcoma, in addition to the low number of patients involved in those studies, have produced inconclusive results. In this review, we have gone through the information available on the role of CD44 in the development, maintenance, and progression of sarcomas, analyzing their implications at the prognostic, therapeutic, and mechanistic levels. Moreover, we illustrate how research involving the specific role of CD44 in the different sarcoma subgroups could suppose a chance to advance towards a more innovative perspective for novel therapies and future clinical trials.